PERBANDINGAN EFEKTIFITAS PEMBERIAN JUS MENTIMUN DAN WORTEL TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI PADA USIA 60-70 TAHUN DESA PEMATANG LALANG - Arifianu Lahagu; Lam Murni Sagala (Indonesian Trust Nursing Journal, 2026)
Hypertension is a major health issue among the elderly as it increases the risk of complications such as stroke and heart disease. Non-pharmacological efforts, such as vegetable juice consumption, are considered an easy and inexpensive alternative, including cucumber and carrot juice, which are rich in nutrients and have the potential to lower blood pressure. This study uses a quasi-experimental design with a pretest-posttest approach involving two groups, consisting of 38 elderly respondents aged 60–70 years in Pematang Lalang Village, divided into cucumber juice and carrot juice group. The results show that cucumber juice reduces systolic blood pressure by an average of 36.06 mmHg and diastolic by 16.84 mmHg, while carrot juice lowers systolic by 30.78 mmHg and diastolic by 6.79 mmHg. Statistical analysis demonstrates a significant difference, where cucumber juice is more effective than carrot juice in lowering blood pressure among hypertensive elderly individuals. Therefore, cucumber juice can be recommended as a more optimal non-pharmacological alternative to help control blood pressure in the elderly.